GAMBARAN ADAPTASI SOSIAL MAHASISWA BARU RANTAU - Isna Fanesa; Dea Fitri; Banati Fitri; Anggi Eli; Tazzida Ilma; Satriya Pranata (PT. Hasba Edukasi Mandiri, 2025)
This study looks at how new migrant nursing students at the Muhammadiyah University of Semarang adapt socially in 2025. Moving from high school to university can be tough, especially for students who are moving to a new place and have to adjust to a different social and learning environment. The research is quantitative and descriptive, and it included 67 participants. Information was gathered through a questionnaire that looked at six areas related to social adaptation. The findings show that most students have a moderate level of social adaptation. Among these areas, social interaction and support were the strongest, but emotional regulation was lower. Universities should work on improving their mentoring programs to help students adjust better in both social and academic settings.